Pengaruh Pengetahuan Pajak Dan Modernisasi Administrasi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Dengan Sosialisasi Perpajakan Sebagai Variabel Moderasi (Studi Kasus Wajib Pajak Orang Pribadi Non Karyawan di DKI Jakarta) - Alya Risdhea Islama Wardhani; Suri Mahrani (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to test and analyze Tax Knowledge and Modernization of Tax Administration on Individual Taxpayers’ Compliance with Tax Socialization as a Moderation Variable with Non-Employee Individual Taxpayers residing in DKI Jakarta as the object of research. The theory used in this study is Theory of Planned Behavior. The sampling method in this study was carried out using the Nonprobability Sampling method using Accidental Sampling. The population in this study is 1.838.096 Non-Employee Individual Taxpayers residing in DKI Jakarta. Meanwhile, the sample used in this study was as many as 100 respondents who were determined using the Slovin formula. Data collection was carried out using a questionnaire. The statistical testing method uses the Smart Partial Least Square (Smart-PLS) application version 4.1.0.3. The results of this study show that Tax Knowledge has an effect on Taxpayer Compliance, Modernization of Tax Administration has an effect on Taxpayer Compliance, Tax Socialization in not able to moderate the influence of Tax Knowledge on Taxpayer Compliance, and Tax Socialization is not able to moderate the influence of Modernization of Tax Administration on Taxpayer Compliance.